Anaerobic digestate water for Chlorella pyrenoidosa cultivation and employed as co-substrate with cow dung and chicken manure for methane and hydrogen production: A closed loop approach. (March 2021) - Malolan, Rajagopal; Jayaraman, Ramesh Sai; Adithya, Srikanth; Arun, Jayaseelan; Gopinath, Kannappan Panchamoorthy; SundarRajan, PanneerSelvam; Nasif, Omaima; Kim, Woong; Govarthanan, Muthusamy
Abstract: In rural India, unpleasant atmosphere, anthropogenic gas emission, air and soil pollution are caused due to disposal of livestock's wastes (cow dung and chicken waste) in open environment. This study provides zero emission concept for waste disposal and value addition of these wastes for renewable green energy production. In this study, biogas production was carried out with varying proportion of cow dung to chicken waste (1:0, 0:1, 1:1, 2:1, 1:2, 3:1 and 1:3) for duration of 40 days. Chlorella pyrenoidosa was cultivated from digestate water and used as co-substrate in digester in varying proportions (2:1:1, 2:1:2 and 2:1:3) to study its role on biogas distribution. The effect of pH, feedstock ratio, time and C/N ratio for biogas production were evaluated. The maximum methane and hydrogen yield was 68% (30th day) and 29% (10th day) for 2:1:2 ratio respectively. The slurry possessed nitrogen (1.7%), phosphate (0.8%) and potassium (0.4%) respectively. Highlights: Green energy from digestion of cow dung and chicken waste with zero discharge. Methane yield was 68% on 30th day with density of 1.27 kg/m 3 for 2:1:2 ratio. Cow dung: chicken waste: algae (2:1:2) resulted 29% of hydrogen yield on 10th day. Slurry can be used as bio-manure due to 1.7% of nitrogen and 0.8% of phosphate.